Survey of Zoonotic Bacterial Pathogens in Native Foxes in Central Chile: First Record of Brucella canis Exposure - Nicolás Galarce; Sebastián de la Fuente; Beatriz Escobar; Phillip Dettleff; Pedro Abalos; Juan Carlos Hormazábal; Roberto Flores; Nicole Sallaberry-Pincheira; Víctor Martínez (Animals, 2021)
Brucella abortus, B. canis, and pathogenic Leptospira are zoonotic pathogens that infect humans, as well as domestic and wild animals. In wild canids, they may affect their fertility and reproduction, threatening their conservation. Wild canids play a crucial role in the environment as meso- and top-predators and environmental sentinels for zoonotic pathogens. In Chile, three species of wild canids are present, and due to changes in land use and environmental dynamics, it is of utmost relevance to determine the role of these species in the epidemiology of brucellosis and leptospirosis. This study aimed to detect the exposure to B. abortus, B. canis, and pathogenic Leptospira by serologic, bacteriologic, and molecular techniques in native foxes from rehabilitation and exhibition centers in Central Chile. Forty-six blood samples were obtained from Lycalopex culpaeus and L. griseus, detecting 10.9% of seropositivity to B. canis and 7.7% to L. Javanica. No seropositivity was seen for B. abortus. Exposure was not registered by culture and qPCR in any of the sampled animals. Our findings are the first register of exposure to any Brucella species in wild canids in Chile and highlight the need to establish surveillance programs of these emerging pathogens.